2019
DOI: 10.1186/s12885-019-5265-5
|View full text |Cite
|
Sign up to set email alerts
|

A rare BCR-ABL1 transcript in Philadelphia-positive acute myeloid leukemia: case report and literature review

Abstract: BackgroundPhiladelphia (Ph) chromosome results from the reciprocal translocation t(9;22)(q34.1;q11.2) and is diagnostic for chronic myeloid leukemia (CML). However, this translocation is also found in acute lymphoid leukemia (ALL), as well as in rare cases of acute myeloid leukemias (AML). Most patients with CML harbor either the e13a2 or the e14a2 BCR-ABL fusion product, while a small subset of the cases expresses e1a2 or e19a2 transcripts. Moreover, several atypical BCR-ABL1 transcripts, beside the most comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
1
12
0
3
Order By: Relevance
“…As mentioned previously, the presence of the Philadelphia gene is a hallmark of CML and only a rare subset of acute myeloid leukemias (AML) (30,31). The barrow in this report appeared to display the standard stages of CML including a relatively insidious disease onset with a chronic phase in which symptoms waxed and waned followed by what might be considered a rapid or accelerated phase that progressed to a fatal blast crisis.…”
Section: Discussionsupporting
confidence: 60%
“…As mentioned previously, the presence of the Philadelphia gene is a hallmark of CML and only a rare subset of acute myeloid leukemias (AML) (30,31). The barrow in this report appeared to display the standard stages of CML including a relatively insidious disease onset with a chronic phase in which symptoms waxed and waned followed by what might be considered a rapid or accelerated phase that progressed to a fatal blast crisis.…”
Section: Discussionsupporting
confidence: 60%
“…The effect of these drugs in the treatment of AML is unclear. However, several studies have suggested the potential of nilotinib as a therapeutic agent for AML that features BCR-ABL1 transcription ( 62 , 63 , 64 ). The potential of fostamatinib as a therapeutic agent in FLT3-ITD–positive AML has been supported by evidence of the importance of SYK in the regulation of FLT3 ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…4,15 Even in the routine detection of FGs that are already well known, false negative results may occur because of variant fusion transcripts, such as BCR-ABL1 and their variant and rare isotypes. 17,18 Therefore, how to effectively identify rare and variant FGs poses great challenges for detection methods and data analysis.…”
Section: Traditional Methods and Limitations Of Fgs Identificationmentioning
confidence: 99%